Taraxacum sect. Orientalia (Compositae-Crepidinae) and the West Himalayan dandelions: A new interpretation - Kirschner, Jan; Štěpánek, Jan; Zeisek, Vojtěch (Phytotaxa, 2017)
The Taraxacum flora of the West Himalaya represents one of the dandelion diversity hotspots, with at least 17 sections and about 150 known species. A number of names published from that region were referred to T. sect. Orientalia Handel-Mazzetti in the literature. All these names are revised and newly interpreted, with emphasis on plants erroneously determined as T. stenolepium. The revision is based on both older herbarium collections and a new material from expeditions of the late L. Klimeš. A new section, T. sect. Squamulosa, is recognized. An nrDNA ITS sequence analysis including the only sexual member of T. section Squamulosa and the other sexual taxa known in Taraxacum shows a separate position of T. sect. Squamulosa. The new section is compared with sections Primigenia, Coronata and Orientalia. Amended descriptions, range extensions and new interpretations are presented for another seven species previously mistakenly referred to T. sect. Orientalia. The true T. sect. Orientalia is analysed and briefly characterized; it is shown to be absent from the West Himalaya.